A new genus of Pycnodontidae (Actinopterygii) from the Upper Jurassic of France and Germany, included in a phylogeny of Pycnodontiformes. Issue 2 (21st October 2019) - Ebert, Martin
Abstract: The new genus Thiollierepycnodus is erected here to accommodate ' Gyrodus ' wagneri or ' Proscinetes ' wagneri, a taxon known since the 19 th century from the marine Kimmeridgian Plattenkalk of Cerin (France) and since 2014 at the excavation site of the Naturkunde-Museum Bamberg in Wattendorf (Germany). Thiollierepycnodus is placed in Pycnodontidae (Upper Jurassic to Eocene), which is the most advanced family of Pycnodontiformes. With 154–152 Myr (Upper Jurassic), Thiollierepycnodus belongs to the stratigraphically oldest Pycnodontidae, still possessing some primitive features such as four incisiform teeth in the dentary, a crown of bifurcated anterior dentary teeth, reduced scale bars posterior to the dorsal fin origin, but the area of pterygiophores without scales and nine to 10 postanal ventral keel scales and approximately 10 complete scale rows posterior to the cloaca. A phylogenetic analysis leads to the placement of this taxon in Proscinetinae. This and the introduction of two additional taxa from the Cretaceous of Lebanon in the phylogeny are further steps to enlighten the broader evolutionary patterns of Pycnodontidae.